Iguratimod prevents renal fibrosis in unilateral ureteral obstruction model mice by suppressing M2 macrophage infiltration and macrophage–myofibroblast transition - Yueyuan Zhou; Zhilan Li; Shenyi Yu; Xuan Wang; Tingting Xie; Weiru Zhang (Renal Failure)
Iguratimod is a novel synthetic, small-molecule immunosuppressive agent used to treat rheumatoid arthritis. Through ongoing exploration of its role and mechanisms of action, iguratimod has been observed to have antifibrotic effects in the lung and skin; however, its effect on renal fibrosis remains unknown. This study aimed to investigate whether iguratimod could affect renal fibrosis progression. Three different concentrations of iguratimod (30 mg/kg/day, 10 mg/kg/day, and 3 mg/kg/day) were used to intervene in unilateral ureteral obstruction (UUO) model mice. Iguratimod at 10 mg/kg/day was observed to be effective in slowing UUO-mediated renal fibrosis. In addition, stimulating bone marrow-derived macrophages with IL-4 and/or iguratimod, or with TGF-β and iguratimod or SRC inhibitors in vitro, suggested that iguratimod mitigates the progression of renal fibrosis in UUO mice, at least in part, by inhibiting the IL-4/STAT6 signaling pathway to attenuate renal M2 macrophage infiltration, as well as by impeding SRC activation to reduce macrophage–myofibroblast transition. These findings reveal the potential of iguratimod as a treatment for renal disease.